2001
DOI: 10.1016/s0014-5793(00)02400-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel type Arabidopsis thaliana H+‐PPase is localized to the Golgi apparatus

Abstract: Vacuolar H + -PPase, a membrane bound protontranslocating pyrophosphatase found in various species including plants, some protozoan and prokaryotes, has been demonstrated to be localized to the vacuolar membrane in plants. Using a GUS reporter system and a green fluorescent protein (GFP) fusion protein, we investigated the tissue distribution and the subcellular localization, respectively, of a novel type H + -PPase encoded by AVP2/AVPL1 identified in the Arabidopsis thaliana genome. We showed that AVP2/AVPL1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 42 publications
2
49
0
Order By: Relevance
“…Like AtSAC1-GFP in Arabidopsis root cells, AtSAC1-enhanced yellow fluorescent protein (EYFP) and AtSAC1-enhanced cyan fluorescent protein (ECFP) displayed punctate localization patterns in carrot protoplasts ( Figure 9). It was found that the punctate pattern of AtSAC1-EYFP was almost identical to the localization pattern of the Golgi marker Arabidopsis proton-translocating pyrophosphatase2 (AVP2) (Figures 9A to 9D) (Mitsuda et al, 2001) but showed obvious differences from those of the prevacuolar membrane marker Ras-related small GTP binding protein1 (Rha1) (Figures 9E to 9H) (Lee et al, 2004) and an ER marker ( Figures 9I to 9L). These results suggest that AtSAC1 is associated with Golgi in the cells.…”
Section: Subcellular Localization Of the Atsac1 Proteinmentioning
confidence: 78%
“…Like AtSAC1-GFP in Arabidopsis root cells, AtSAC1-enhanced yellow fluorescent protein (EYFP) and AtSAC1-enhanced cyan fluorescent protein (ECFP) displayed punctate localization patterns in carrot protoplasts ( Figure 9). It was found that the punctate pattern of AtSAC1-EYFP was almost identical to the localization pattern of the Golgi marker Arabidopsis proton-translocating pyrophosphatase2 (AVP2) (Figures 9A to 9D) (Mitsuda et al, 2001) but showed obvious differences from those of the prevacuolar membrane marker Ras-related small GTP binding protein1 (Rha1) (Figures 9E to 9H) (Lee et al, 2004) and an ER marker ( Figures 9I to 9L). These results suggest that AtSAC1 is associated with Golgi in the cells.…”
Section: Subcellular Localization Of the Atsac1 Proteinmentioning
confidence: 78%
“…Interestingly, sugar-responsive cis-elements (i.e. AMY, BOX1 and -2 CGACG boxes) are present in the regulatory region of the AVP1 promoter (Mitsuda et al, 2001). Up-regulation of H + -PPase genes has been reported in Suc-starved cells of rice (Wang et al, 2007).…”
Section: The Sugar and Phosphate Connectionmentioning
confidence: 99%
“…TgM2AP⌬pro also overlapped with TgVP1, a "vacuolar" proton pyrophosphatase ( Figure 5D). Vacuolar proton pyrophosphatases acidify intracellular compartments, including digestive (Zhen et al, 1994) or contractile vacuoles (Montalvetti et al, 2004), acidocalcisomes (Montalvetti et al, 2004), or the trans-Golgi (Mitsuda et al, 2001) by using pyrophosphate hydrolysis to drive the translocation of protons across endomembranes.…”
Section: The Tgm2ap Propeptide Is Probably Not Required For Folding mentioning
confidence: 99%